APLIKASI GAME EDUKASI PUZZLE DENGAN KECERDASAN BUATAN BERBASIS ANDROID - Markani Kania (LPPM Universitas Al Asyariah Mandar, 2021)
ABSTRACT This study aims to see the designer and implementation of a puzzle educational game application with artificial intelligence using a finite state machine (FSM) and android-based random shuffle based on android. The data research method is by browsing the internet, studyng books, journals, theses, and SWOT system analysis. The shuffle random algorithm for randomizing puzzles and game agents uses a control system (finite state machine) FSM as AI (artificial intelligence). UML method (integrated modeling language). The results of this research application of fruit, animal, and transportation name recognition games in the form of .APK and run on an android smartphone, educational games